1979
DOI: 10.1111/j.1365-2672.1979.tb02588.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of Bacterial Proteins from Cellulosic Materials

Abstract: An aerobic mesophilic Pseudomonas sp. isolated from activated sludge degraded different cellulosic materials to varying‐degrees. The degradability was mostly influenced by the lignin content and the crystalline nature of the substrate. Filter paper and cotton fibres, containing little lignin, were degraded maximally. Lignin‐rich Pinus and Larix needles were digested to a lesser extent. There was a difference between natural substrates and substrates that had undergone industrial treatment. At maximal protein p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1979
1979
1987
1987

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The results showed that -95% of the whey lactose w2s metabolized within 8 h in both mixed fermentations ( Fermentation times are considerably shorter than those previously described for animal waste fermentations (Ramasamy et al, 1979;Weiner and Rhodes, 1974;Weiner, 1977a). …”
Section: And Discussionmentioning
confidence: 85%
“…The results showed that -95% of the whey lactose w2s metabolized within 8 h in both mixed fermentations ( Fermentation times are considerably shorter than those previously described for animal waste fermentations (Ramasamy et al, 1979;Weiner and Rhodes, 1974;Weiner, 1977a). …”
Section: And Discussionmentioning
confidence: 85%
“…Experiments are in progress to determine whether such a recycling via the external microflora occurs. Other bacteria that were common in the isopod and wood microfloras include Vibrio, Pseudomonas, and Acinetobacter species (Table 3), and these have been shown to hydrolyze cellulose (1,8,19,27,28,44,49). In addition to their cellulolytic capabilities, some Vibrio strains are known to hydrolyze chitin, the main component of isopod and other crustacean exoskeletons (11,49).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria have a faster growth and a higher rate of proteins than fungi. Most of the recent papers published concerned strains of the genera Cellulomonas [l-31, Pseudomow [4] or complex undefined mixed cultures [5] but the genus Cellulomonas is generally considered as the best cellulolwytic one [6]. Bacteria of this genus can degrade microcrystalline cellulose [7] as well as fungi, but also hemicelluloses [8] with high yields of protein, over than 55% [9] of the dry weight.…”
Section: Introductionmentioning
confidence: 99%